2014
DOI: 10.11606/issn.2316-9028.v8i2p265-284
|View full text |Cite
|
Sign up to set email alerts
|

Mammogram Diagnostics via 2-D Complex Wavelet-based Self-similarity Measures

Abstract: Breast cancer is the second leading cause of death in women in the United States. Mammography is currently the most eective method for detecting breast cancer early; however, radiological inter- pretation of mammogram images is a challenging task. Many medical images demonstrate a certain degree of self-similarity over a range of scales. This scaling can help us to describe and classify mammograms. In this work, we generalize the scale-mixing wavelet spectra to the complex wavelet domain. In this domain, we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…For fractional Brownian motion, we observe that our method achieves gains in mean square error, albeit at a cost of a decrease in bias performance. These results agree with other studies using complex-valued wavelet methodology, which is shown to outperform its real-valued counterpart in a variety of applications, from denoising (Barber and Nason 2004 to Hurst estimation in the (real-valued) image context (Nelson and Kingsbury 2010;Jeon et al 2014;Nafornita et al 2014). This is due to the use of two rather than just one filter, thus eliciting more information from the signal under analysis.…”
Section: Simulated Performance Of Clompesupporting
confidence: 89%
See 1 more Smart Citation
“…For fractional Brownian motion, we observe that our method achieves gains in mean square error, albeit at a cost of a decrease in bias performance. These results agree with other studies using complex-valued wavelet methodology, which is shown to outperform its real-valued counterpart in a variety of applications, from denoising (Barber and Nason 2004 to Hurst estimation in the (real-valued) image context (Nelson and Kingsbury 2010;Jeon et al 2014;Nafornita et al 2014). This is due to the use of two rather than just one filter, thus eliciting more information from the signal under analysis.…”
Section: Simulated Performance Of Clompesupporting
confidence: 89%
“…Recent works that deal with long memory estimation in various settings are Vidakovic et al (2000), Shi et al (2005), Hsu (2006), Jung et al (2010) and Coeurjolly et al (2014). Some authors have recently considered Hurst estimation using complexvalued wavelets in the regularly spaced real-valued image context; see Nelson and Kingsbury (2010), Jeon et al (2014) and Nafornita et al (2014). Reviews comparing several techniques for Hurst exponent estimation (for real-valued series) can be found in, for example, Taqqu et al (1995).…”
Section: Long Memory and Its Estimationmentioning
confidence: 99%
“…Extensions of wavelet estimators to other settings, for example the presence of observational noise, can be found in Stoev et al (2006), Gloter and Hoffmann (2007). Other recent works concerning long-memory estimation including multiscale approaches are Vidakovic et al (2000), Shi et al (2005), Hsu (2006), Jung et al (2010), Coeurjolly et al (2014) and Jeon et al (2014). Reviews comparing several techniques for Hurst exponent estimation can be found in e.g.…”
Section: Review Of Long-range Dependence Its Estimation Wavelets Anmentioning
confidence: 99%
“…A 2014 study using the discrete complex wavelet transform on mammogram images obtained a classification procedure based on the spectral slopes and phase variance of mammograms with and without cancer with an accuracy rate of nearly 86% [8]. However, it was later discovered that the mammograms of the cases were performed on a different mammography unit than the mammograms of the controls.…”
Section: Introductionmentioning
confidence: 99%